South Africa : Financial Sector Assessment Program-Detailed Assessment of Observance on the Insurance Core Principles. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses key findings of the Detailed Assessment of Observance on the Insurance Core Principles on South Africa. Insurance regulatory and supervisory regime in South Africa is in transition. Currently, the Financial Services Board (FSB-SA) regulates the nonbanking financial services industry, including the insurance sector, in South Africa. With the goal of achieving a safer financial sector to serve South Africa better, the government has proposed major changes in the financial sector. The four policy objectives are: financial stability, consumer protection and market conduct, financial inclusion, and combating financial crime. Market realities in the insurance sector pose significant regulatory challenges, which are well recognized by the authorities.